REPORT OF THE ANNUAL CONVENTION. - Gaa, Charles J. (The Accounting Review, 1952)
The Annual Business Meeting of the members of the American Accounting Association was conducted as part of two regularly scheduled sessions of the 1951 Convention. During the banquet session on September 6, 1951 officers for 1952 were elected. The remaining business was handled during the regular business session on September 7, 1951. Mr. A. C. Bekaert, Vice President of the Colorado Fuel and Iron Corp. addressed the members and guests at the banquet on the subject of clarification of terminology used in financial statements. It was announced that registrations at the convention made through the middle of the first day were 302 men and 102 ladies. The total attendance at the several sessions was about 500. Mr. Harvey Meyer of the University of Tennessee, Knoxville, Tennessee presented the report of the nominating committee. The new officers were introduced and George R. Husband of Wayne University, Detroit, Michigan made an acceptance speech, on behalf of elected members. The report of the committee on by-laws was presented by chairman Harvey Meyer; it proposed an extensive editorial revision of the language of the by-laws in the interest of clarification, plus a few minor substantive changes. After some discussion, the report of the committee on by-laws was approved unanimously.